In the wake of Brexit: negotiating diversity and majority-minority relations in the North of England. Issue 8 (9th May 2023) - Wallace, Andrew; Favell, Adrian
ABSTRACT: Our contribution to this special issue brings the theoretical and empirical orientations of the Becoming a Minority ( BaM ) project into dialogue with the complex and charged post-Brexit geography of the North of England. We present findings from the UK ESRC funded project Northern Exposure: Race, Nation and Disaffection in 'Ordinary' Towns and Cities after Brexit, drawing upon a period of co-productive and ethnographic work with local authority stakeholders, voluntary sector practitioners and community actors in two urban locations in the English North: Halifax and Wakefield. We report on how shifting patterns of diversity and population change interlock with deindustrialised economies, fiscal austerity, the coronavirus crisis, and the predations of ethno-nationalist politics and policy. Amid these dislocations and risks, we find delicate, differentiated, and predominantly informal infrastructures of community governance and intervention attempting to build alliances and resolve tensions: a grounded, local-view that belies the kind of image of the North established in mainstream national understandings of the dramatic politics of Brexit and after. Taking a productive cue from the BaM study, we offer some fine-grained reflections on localised dynamics of diversity experience and the negotiation of inter-ethnic relations albeit in a sprawling urban region beyond the West-European metropolitan core.